PERANAN ULAMA DALAM PENYEBARAN AJARAN ISLAM DI PULAU BESAR, MELAKA (The Role of Muslim Scholars in Spreading the Teaching of Islam in Pulau Besar, Melaka) - Meerangani, Khairul Azhar (Journal of Al-Tamaddun, 2019)
Pulau Besar is one of hotspots in Malacca which is widely associated with mystic and legendary stories. Local and foreign tourists frequently go to the island for various purposes and needs. Despite being more famous with mystical stories, this island indeed one of the main locations for the spread of Islam in Malacca years before. The presence of sufism scholars from the Arab continent such as Syeikh Ismail and Syeikh Yusuf turned out to have succeeded in altering the religious beliefs among the local community. The study aims to examine the roles and contributions played by the scholars of Sufism in the spread of Islam in Pulau Besar, Melaka. Historical facts are derived from primary and secondary sources which are then inductively analyzed to formulate their role in spreading Islam among local communities. The uniqueness of the da’wah delivered had attracted the locals to learn more about the teachings of Islam. The existence of the madrasah in Pulau Besar made the island as one of the learning center and dissemination of Islam in Nusantara. The madrasah also produced a number of prominent figures in Islamic propaganda like Sunan Giri and Sunan Bonang who were finally continue this da’wah effort throughout Nusantara. Apparently, these Sufi scholars have played a significant role in the spread of Islam particularly in Melaka and throughout the entire Nusantara.